Toddler home math environment: Triangulating multi-method assessments in a U.S. Sample - Miller, Portia; Elliott, Leanne E.; Podvysotska, Tamara; Ptak, Chelsea; Duong, Shirley; Fox, Danielle; Coulanges, Linsah; Libertus, Melissa; Bachman, Heather J.; Votruba-Drzal, Elizabeth (Frontiers in Psychology, 2023)
Current research has documented the home math environment (HME) of preschoolers and kindergarteners. Very few studies, however, have explored the number and spatial activities in which parents engage with children during their toddler years. This study examined the HME of 157 toddlers using several methodologies, including surveys, time diaries, and observations of math talk. Further, it examined correlations within and across data sources to identify areas of convergence and triangulation. Findings showed that, in general, within method, uses of different types of math activities, including both number and spatial, were intercorrelated. Across method, there was high intercorrelation between the frequency of math activities reported on parent surveys and the diversity of types of math activities endorsed in time diary interviews. Math talk gleaned from semi-structured interactions functioned as a separate aspect of the HME; different types of math talk shared few intercorrelations with engagement in math activities as reported in either surveys or time diaries. Given extant research demonstrating that both math activities and math talk predict children’s math skills, our results stress the need for multimethod studies that differentiate among these HME opportunities.